Determination of the hypocolesterolemic and anti-stereocherotic effect of aquatic fruit extract Solanum melongena “berenjena” in Rattus norvegicus var. Wistar with experimental hyperlipemia. - Luis Enrique Moncada Bernedo (2020)
The lipid-lowering activity of the aqueous extract of Solanum melongena “berenjena” fruit in Rattus norvegicus Wistar variety with experimental hyperlipidemia was evaluated. It was carried out in the Animal Physiology Laboratory of the National University of San Agustín and Bioterio of the Universidad Católica de Santa María from June 1 to September 31, 2015. 24 Rattus norvegicus Wistar variety distributed in four groups of 6 rats each were used: a hypercholesterolemic control treatment and three experimental Solanum melongena treatment at a dose of 0.5 g / kg / day, 1 g / kg / day and lovastatin at a dose of 3 mg / kg The Wiener method was used in the determination of Total Cholesterol, Triglycerides, HDL-cholesterol and LDLcholesterol. Hyperlipidemia was achieved with a mixture of 50 g of boiled beef brain with 50 g of rabbits plus 3 ml of lard per rat. A significant decrease (p <0.01) was observed in cholesterol, triglyceride and atherogenic index levels and a significant increase in HDL-C levels, compared to the control group. The results show us that the administration of 0.5 and 1 g / kg / day of aqueous extract of Solanum melongena “berenjena” decreases the levels of total cholesterol and triglycerides in Rattus norvegicus Wistar variety with experimental hyperlipidemia. It also has no hepatotoxic effect and reduces atheromatous plaques in the aorta.